A hora da roda e o juízo moral na criança - Oliveira, Bianca de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The everyday from kindergartens are made of a compound of lasting activities that comply with the needs of fully education and care among the children. One of those activities is the circle time, which is capable of developing the children's moral judgement when realized in a planed way with clear intentions and interventions made by the professor. This empirical descriptive research intends to investigate how the circle time have been developed in kindergarten institutions and what are the professors conceptions about the theme in a way that proposes the circle time as a propitious environment to developing children's moral autonomy. Two municipals schools from Bauru-SP were part of the research, abording two classes, with children ages 4-5 and it's professors. The observations, interviews and moral dilemas interventions were the data picking for the data basing. It was possible to prove that at the circle time rise a variety of moral themes on top of the existing conflicts and that it's achievable abording it with real or hypothetical situations. The professors share the importance on the realization of a work that fulfill the moral construction of the children and also they saw the circle time as a privileged moment to have the theme on board. However, there are fragilities in professional formation that reflects in the way of organizing and building the circle. It has been confirmed that children's behavior suffers big influence from the sociomoral environment established in class and that the work with moral dilemas enabled an understanding of the moral rationality in the children's scenario of solving problems, realizing that they engaged in socially positive behaviors, nevertheless they need to be capacitated to face interpersonal questions in a self-governing way. It has been highlighted the importance in actualizing a work in kindergarten children...

O cotidiano das escolas de Educação Infantil é composto de atividades permanentes que atendem às necessidades de cuidar e educar de forma integrada, uma delas é a hora da roda capaz de desenvolver o juízo moral das crianças, quando realizada de forma planejada, com objetivos claros e intervenções refletidas por parte do professor. Esta pesquisa empírico-descritiva buscou investigar como a hora da roda tem sido desenvolvida nas instituições de Educação Infantil e quais as concepções dos professores sobre o tema, a fim de propor a hora da roda como um espaço propiciador do desenvolvimento da autonomia moral das crianças. Participaram da pesquisa duas Escolas Municipais de Bauru/SP abrangendo duas turmas de crianças entre 4-5 anos de idade e suas respectivas professoras. Como instrumento para coleta de dados utilizou-se a observação, a entrevista e a intervenção com dilemas morais. Foi possível comprovar que no decorrer da roda surgem temas morais variados a partir dos conflitos existentes e que é possível abordá-los por meio das situações reais ou hipotéticas. As professoras partilham da importância de realizar um trabalho que contemple a construção moral das crianças e reconhecem a hora da roda como um momento privilegiado para abordar o tema. No entanto, encontram-se fragilidades na formação profissional que refletem na forma de organizar e compor a roda. Confirmou-se que o comportamento das crianças é influenciado pelo ambiente sociomoral estabelecido na classe e que o trabalho com dilemas morais possibilitou a compreensão do raciocínio moral das crianças na resolução de conflitos, percebendo que elas se engajam em comportamentos pró-sociais, porém, é preciso capacitá-las para enfrentar questões interpessoais de modo autônomo. Verificou-se a importância de se efetivar um trabalho na Educação Infantil que privilegie a dimensão moral do desenvolvimento...
Keywords: Educação de crianças; Aprendizagem; Educação pre-escolar